USING THE COMMUNICATIVE LANGUAGE TEACHING METHOD TO IMPROVE THE STUDENTS’ ENGLISH SPEAKING FLUENCY - Rachma Ayulisjati; Mustasyfa Thabib Kariadi; Prayogo Hadi Sulistio (LEAD (Language, Education and Development), 2021)
The research entitled “Using the Communicative Language Teaching Method to Improve the Students’ English Speaking Fluency” aims to examine the implementation of CLT method in the classroom, figure out the students’ improvement in English speaking fluency, and reveal the influencing factors after the implementation of CLT method. This research used the quasi experimental design. The subjects of this research were the eleventh grade students of SMAN 4 Purwokerto in the academic year of 2019/2020. The population was 340 students divided into 10 classes. The samples of this research were two classes: XI MIPA 1 as the experimental group and XI MIPA 3 as the control group. The data were collected from observations, questionnaires, and tests. The result of this research shows that the implementation of CLT method was successful. It can be seen from the observation sheet that the teacher followed the implementation of CLT method, such as the teacher had prepared the materials well; the materials were approved by the teacher which based on the syllabus and curriculum; the teacher clearly gave the instructions; the teacher asked the students to speak freely, encouraged the students to speak in English, fully spoke in English, and provided the appropriate tasks to improve the students’ speaking fluency. Furthermore, the students’ English speaking fluency has improved. It means that the implementation of CLT method has significant effect that the alternative hypothesis (Hi) is accepted. The result of questionnaires and observations show that the factors influencing the implementation of CLT method were cognitive, linguistic, and affective factors.